MENENTUKAN HARGA KONTRAK BERJANGKA KOMODITAS KEDELAI MENGGUNAKAN MODEL MEAN REVERSION - SEDANA, WIRYA; DHARMAWAN, KOMANG; ASIH, NI MADE (E-Jurnal Matematika, 2016)
It has been discussed in many literatures that commodity prices tend to follow mean reversion model. This means that when there is a jump price in certain time, the price will revert to the mean price in the future. In this research, the method to determine the existence of mean-reversion of soybean price dynamics is discussed. Then, the future contract of soybeans is calculated using mean-reversion simulation and the spot-future parity theorem. Both methods are applied to the closing price of soybeans for the period of 19 September 2011 to 28 April 2016. The results show that the future contract price calculated by Model Mean-Reversion simulation under estimate the future contract price determined by the spot-future parity theorem.
Keywords: Derivative securities; futures contract; soybeans commodity; Model Mean Reversion; Spot-futures parity theorem